RICE FOR NUTRITION: A TEMPORAL PERSPECTIVE OF THE MAJOR SAARC COUNTRIES - Subrato Kumar Kuri; Md. Jamal Hossain; Upama Mondal (European Scientific Journal, ESJ, 2014)
Rice is the major source of nutrition in most of the South Asian countries. This paper examined the rice contribution status on nutrition supply viz. calorie, protein and fat from 1975 to 2009 among the major SAARC (South Asian Association for Regional Cooperation) countries. Among the major SAARC countries the people of Bangladesh highly relied on rice for calorie (72%), protein (62%) and fat supplies (17%) to meet their nutritional needs although it has not achieved yet rice yield sufficiency. It was found that India is the highest rice producer among the SAARC countries but they consume very littile amount of rice for their nutritional needs. It indicated that Bangladesh has been practicing rice monoculture widely and their food habit is rice based due to lack of variety of crop species. So it is needed to produce different crops like wheat, maize, potato and other fruits and vegetables for consumption. As well, poultry and livestock sectors have to be developed for more protein and fat supply from other sources along with rice in Bangladesh.